A Comprehensive Study on Narcos Analysis Using Deep Learning - G. Thippanna, P. Murthuja, K. Samunnisa (Mathematical Statistician and Engineering Applications, 2023)
The advancement of technology, increased individual freedom, a loss in the power of society, church, and family, and an increase in crime intensity have made criminal investigations more difficult. Always adapt the law to social developments. To deal with evolving crimes and offender techniques, the criminal justice system must evolve. Investigative organisations are employing a number of modern tools to get the truth from offenders and eyewitnesses. Most extensively used tests worldwide, including India, are Lie Detector, BEAP, and Narco-analysis. The use of narco-analysis testing in criminal investigations is a contentious issue. Mathematical functions are employed in Deep Learning to map input to output. In order to connect input and output, these functions extract non-redundant data or patterns.